MEDAN DENTIST’S KNOWLEDGE LEVEL ABOUT ORAL SQUAMOUS CELL CARCINOMA ASSOCIATED HUMAN PAPILLOMAVIRUS - Sayuti Hasibuan; Sal Sabila Aulia Rahma (Universitas Baiturrahmah, 2023)
Introduction: Oral Squamous Cell carcinomas (OSCC) are still common, and one of the causes is the human papillomavirus (HPV). OSCC-associated HPV is often detected at an advanced stage due to the low knowledge of dentists about early detection. A good level of knowledge among dentists will help reduce the incidence of OSCC- associated HPV cases. This study aims to determine the level of knowledge of general dentists in Medan City regarding the role of HPV in OSCC, clinical aspects, prognosis, preventive measures for OSCC- associated HPV, and the availability of HPV vaccines in Indonesia. Method: This research is a descriptive study with a cross-sectional approach; the number of respondents is 99 general dentists in Medan City. The data was collected using an online questionnaire. Data analysis was carried out descriptively and calculated in terms of frequency and percentage through SPSS. Result: The results showed that among the 99 respondents, the level of knowledge about the role of HPV in OSCC was good (98%). The level of knowledge regarding the clinical aspects of OSCC-associated HPV is good (64.6%). The level of knowledge regarding the prognosis of OSCC-associated HPV is adequate (70.7%). The level of knowledge regarding OSCC- associated HPV preventive action is good (79.8%). The level of knowledge regarding the availability of the HPV vaccine in Indonesia is good (67.7%). Conclusion: Based on the results of the study, the level of knowledge of general dentists in Medan City about Oral Squamous Cell Carcinoma (OSCC) related to Human Papillomavirus (HPV) is good (66.7%).